(3GdeSFhdjI GdLfGFjI ddeUGHjf HGdCeQGV GdYUHjI hGdfaSjI (B/ s - (3YUGe eMehO YHOGdMdje jhSa s; (3CMeO YhV HdGds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JWQbJ gPg GdOQGSI Edi HMK eSCdI GdeLQe GdeUGH HGVWQGH faSj Ch Ybdj(B: (3GdJj JYO ef CcKQ GdeSGFd LOdkG aj GdbGfhf dCfgG Jba Ydi MOhO GdWH GdfaSj(B: (3bGfhf GdeSFhdjI GdLfGFjI hYde GdELQGe(B. (3hgPG eG jJWdH JYGhf QLd GdbGfhf hQLd GdWH aj gPG GdeLGd(B: (3dGf dcdjgeG OhQ jdYHg(B. (3aGdChd jVY GdfUhU GdbGfhfjI hjWHbgG BNPG aj GdMSHGf GdMGdI GdYbdjI ddTNU; hGdKGfj jJhdi GdYdGL GdWHj hGdQYGjI GdfaSjI dg(B. (3aGdOGQSGJ GdbGfhfjI (B{u(32013(B} (3HUhQI YGeI (B{u(32013(B} (3dG jecf GdfXQ EdjgG HeYRd Yf GdOGQSGJ GdEfSGfjI GdadSajI hGdfaSjI hcPdc GdOGQSGJ GdYdejI hGdWHjI Pdc Cf GdEfSGf gh eMhQ LejY gPg GdOGQSGJ(B: (3hef gfG cGfJ CgejI GdQHW aj gPg GdOGQSI Hjf GdOGQSGJ GdSGHbI(B: (3ef CLd GdhUhd Edi JfXje bGfhfj CcKQ JWhQG jfXe CKQ GdGVWQGHGJ GdfaSjI hGdYbdjI Ydi GdeSFhdjI GdLfGFjI(B. (3hbO Je Pdc ef NdGd GdJWQb Edi aUd JegjOj Yf eGgjI GdeSFhdjI GdLfGFjI hOYGFegG(B: (3hHGHjf(B: (3GdGVWQGHGJ GdfaSjI hGdYbdjI heOdhdGJgG GdWHjI hGdbGfhfjI(B: (3GdOaY HYOe GdeSFhdjI HSHH GVWQGH faSj Ch Ybdj hBKGQg Ydi GdeLQejf GdThGPs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B536-557s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdCeQGV GdYUHjI hGdfaSjIs; (3GdeSFhdjI GdLfGFjIs; (3eSCdI GdeLQes; (3GdGVWQGH GdYbdjs; (3GdghSs; (3GdGcJFGH s; (3GdUQYs; (3GdThGPs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs